Material with high dielectric constant and low dielectric loss and preparation method thereof
By using materials such as SPS resin and modified glass fiber, materials with high dielectric constant and low dielectric loss were prepared, which solved the problem that existing materials could not meet the conditions of high dielectric constant and low dielectric loss, and improved the signal quality and stability of wireless communications.
Patent Information
- Application Number
- CN202510139620.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-18
AI Technical Summary
The existing materials for some antenna preparation cannot meet the conditions of high dielectric constant and low dielectric loss, which affects the efficiency and stability of signal transmission.
Materials with high dielectric constant and low dielectric loss are prepared by extrusion granulation process using SPS resin and specially modified glass fibers.
It improves the transmission efficiency and signal quality of RF devices, reduces energy loss and signal attenuation, thereby improving the stability and reliability of wireless communication.
Smart Images

Figure CN119842167A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a high dielectric constant and low dielectric loss material and a preparation method thereof. Background Art
[0002] High dielectric constant and low dielectric loss refers to the property that the dielectric constant of the material is high, but the loss generated during the electromagnetic wave transmission process is low. The dielectric constant is a parameter that describes the material's ability to respond to the electric field, while the dielectric loss is the energy loss generated by the material under the action of the electric field. Materials with high dielectric constant and low dielectric loss have important application value in the fields of electronic communications, radio transmission, microwave technology, etc. In the field of electronic communications, materials with high dielectric constant and low dielectric loss are often used to manufacture high-frequency circuits and antennas.
[0003] For example, the patent with publication number CN103408876A discloses a flexible composite dielectric material with high dielectric constant and low dielectric loss, which is composed of nanofibers of a fluorine-containing polymer matrix and an inorganic titanate dielectric filler surface-modified by fluorosilane; the volume fraction of the fluorine-containing polymer in the composite material is 75v%-95v%, and the volume fraction of the fluorosilane-modified BaTiO3 or MgTiO3 nanofibers in the composite material is 5v%-25v%; the material can significantly improve the dielectric constant of the composite dielectric material and reduce its dielectric loss at the same time, overcoming the shortcomings of the existing organic / inorganic composite technology that while obtaining a high dielectric constant, it will lead to increased dielectric loss; high-frequency circuits require materials with a higher dielectric constant because the capacitance of the capacitor is proportional to the dielectric constant. The operating frequency of the antenna is usually high, which requires the material to have a low dielectric loss. Materials with high dielectric constant and low dielectric loss can improve the transmission efficiency and signal quality of RF devices, reduce energy loss and signal attenuation, thereby improving the stability and reliability of wireless communications. However, some existing materials for making antennas cannot meet the conditions of high dielectric constant and low dielectric loss, affecting the efficiency and stability of signal transmission.
[0004] In view of the above problems, it is urgent to carry out innovative designs based on the original polymer materials. Summary of the invention
[0005] The purpose of the present invention is to provide a high dielectric constant and low dielectric loss material and a preparation method thereof, so as to solve the problem mentioned in the above background technology that some existing materials for preparing antennas cannot meet the conditions of high dielectric constant and low dielectric loss, affecting signal transmission efficiency and stability.
[0006] SPS (syndiotactic polystyrene) material has excellent high temperature resistance and dimensional stability; it can remain stable at higher temperatures, reaching a high temperature of more than 200 degrees when in use, and up to more than 400 degrees; its amorphous glass transition temperature and crystalline melting point are higher than nylon 66, PET, etc., which means that during processing and use, SPS material can maintain good dimensional stability; SPS plastic is not easily corroded by various acids and alkalis, and also has excellent corrosion resistance to oils, refrigerants, etc. related to the automotive environment.
[0007] The dielectric properties of SPS are close to those of fluorine resins among engineering plastics. It has lower dielectric loss and dielectric constant, and is suitable for use as a material for high-frequency parts. SPS material has high fluidity and can be processed and molded by standard injection molding machines. The shrinkage difference of the molded parts in the flow direction (MD) and vertical direction (TD) of the injection resin is very small, and it has good dimensional stability retention performance.
[0008] In summary, SPS material is an excellent material choice for base station antennas. At the same time, its dielectric constant needs to be modified to change its low dielectric constant characteristics. It is urgent to develop high dielectric and low loss materials for 5G / 6G antenna materials.
[0009] To achieve the above object, the present invention provides the following technical solution: a high dielectric constant and low dielectric loss material and a preparation method thereof, wherein the high dielectric constant and low dielectric loss material comprises the following materials:
[0010] SPS resin, the weight percentage content is 75-90%.
[0011] Special fiber, the weight percentage is 5-50%.
[0012] Toughening agent, the weight percentage content is 1-3%.
[0013] Nucleating agent, the weight percentage content is 0.1-0.5%.
[0014] Lubricant, content by weight is 0.1-0.5%.
[0015] Antioxidant, content by weight is 0.2-0.5%.
[0016] The dielectric constant enhancer has a weight percentage of 5-20%.
[0017] Other materials, the weight percentage content is 0.6-2%.
[0018] Preferably, the SPS resin is para-polystyrene. The dielectric properties of SPS resin materials are close to those of fluorine resins in engineering plastics, and the dielectric loss and dielectric constant are low, so SPS resin materials are suitable for use as high-frequency component materials.
[0019] Preferably, the special fiber is a specially modified glass fiber; the dielectric constant of the glass fiber is ε=12-15; the dielectric loss tangent of the glass fiber is tgδ=0.004; the breakdown voltage strength range of the glass fiber is 63-119.5 kilovolts, and the glass fiber can maintain stable dielectric properties at high frequencies; the glass fiber has the performance of high dielectric constant and low dielectric loss at high frequencies of 1-10 GHz, while reducing the density of the glass fiber, which is conducive to product miniaturization and portable applications.
[0020] Preferably, the nucleating agent is a calcium carboxylate salt with a long carbon chain as the main component.
[0021] Preferably, the lubricant is high temperature resistant silicone powder.
[0022] Preferably, the antioxidant is triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl) acrylonitrile, tris(2,4-di-tert-butylphenol) phosphite, or a mixture of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylphenyl) phosphite in a weight ratio of 1:1.
[0023] Preferably, the main raw materials of the dielectric constant enhancer are niobium pentoxide, cobalt tetroxide, nano-barium titanate, a mixture of niobium pentoxide (Nb2O5) and cobalt tetroxide (Co3O4), and barium titanate (BaTiO3, BT), zirconium oxide, and dielectric grade titanium dioxide as dopants; niobium pentoxide has a high dielectric constant, ε=1000, and the bonds between niobium pentoxide atoms are tight, so electrons can easily stay between atoms.
[0024] Preferably, the other materials include a compatibilizer, and the compatibilizer is PPO grafted with maleic anhydride.
[0025] A high dielectric constant and low dielectric loss material, and a preparation method are also disclosed, the specific method steps are as follows:
[0026] S1. Prepare materials.
[0027] S2. preparing a mixed material.
[0028] S3, extruding and granulating the mixture to obtain SPS material.
[0029] Preferably, the mixed material is extruded and granulated by a twin-screw extruder; the temperatures of the mixed material in each section from the feeding port to the die head of the twin-screw extruder are: 220-240°C in zone one, 250-260°C in zone two, 250-260°C in zone three, 250-270°C in zone four, 250-270°C in zone five, 220-240°C in zone six, 220-240°C in zone seven, 240-260°C in zone eight, and 250-280°C in die head; the speed of the screw of the twin-screw extruder is 280-350 rpm.
[0030] Compared with the prior art, the beneficial effects of the present invention are: the SPS material prepared by the high dielectric constant and low dielectric loss material has excellent physical and mechanical properties, high dielectric constant and low dielectric loss, improves the transmission efficiency and signal quality of radio frequency devices, reduces energy loss and signal attenuation, and thus improves the stability and reliability of wireless communications. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a material performance test table of the present invention. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The present invention provides the following technical solution: a high dielectric constant and low dielectric loss material and a preparation method thereof, wherein the high dielectric constant and low dielectric loss material comprises the following materials:
[0034] SPS resin, the weight percentage content is 75-90%.
[0035] Special fiber, the weight percentage is 5-50%.
[0036] Toughening agent, the weight percentage content is 1-3%.
[0037] Nucleating agent, the weight percentage content is 0.1-0.5%.
[0038] Lubricant, content by weight is 0.1-0.5%.
[0039] Antioxidant, content by weight is 0.2-0.5%.
[0040] The dielectric constant enhancer has a weight percentage of 5-20%.
[0041] Other materials, the weight percentage content is 0.6-2%.
[0042] SPS resin is para-polystyrene. The dielectric properties of SPS resin materials are close to those of fluorine resins in engineering plastics. It has low dielectric loss and dielectric constant and is suitable for use as a material for high-frequency parts.
[0043] Special fiber is specially modified glass fiber; the dielectric constant of glass fiber is ε=12-15; the dielectric loss tangent of glass fiber is tgδ=0.004; the breakdown voltage strength range of glass fiber is 63-119.5 kV, and glass fiber can maintain stable dielectric properties at high frequencies; glass fiber has high dielectric constant and low dielectric loss performance at high frequencies of 1-10 GHz, while reducing the density of glass fiber, which is conducive to product miniaturization and portable applications.
[0044] The nucleating agent is a calcium salt of carboxylic acid with a long carbon chain as the main component.
[0045] The lubricant is high temperature resistant silicone powder.
[0046] The antioxidant is triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl) acrylonitrile, tris(2,4-di-tert-butylphenol) phosphite or a mixture of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylphenyl phosphite) in a weight ratio of 1:1.
[0047] The main raw materials of the dielectric constant enhancer are niobium pentoxide, cobalt tetroxide, nano-barium titanate, a mixture of niobium pentoxide (Nb2O5) and cobalt tetroxide (Co3O4), barium titanate (BaTiO3, BT), zirconium oxide, and dielectric grade titanium dioxide, ε=1000, the bonding between niobium pentoxide atoms is tight, and electrons easily stay between atoms.
[0048] Other materials include a compatibilizer, which is PPO grafted with maleic anhydride.
[0049] A high dielectric constant and low dielectric loss material, and a preparation method are also disclosed, the specific method steps are as follows:
[0050] S1. Prepare materials.
[0051] S2. preparing a mixed material.
[0052] S3, extruding and granulating the mixture to obtain SPS material.
[0053] The above-mentioned SPS material preparation method is to mix the components in proportion, and then obtain the product through extrusion granulation treatment. The process is simple, easy to control, low in cost, and suitable for industrial production.
[0054] In step S2 of the SPS material preparation method, the components are mixed according to the formula. The mixing method can be that the components are put into a mixer and mixed thoroughly. The mixing time is preferably 20 to 30 minutes, so that the components are mixed evenly.
[0055] In step S3 of the SPS alloy material preparation method, the mixed material is extruded and granulated by a twin-screw extruder; the temperatures of the mixed material in each section from the feeding port to the die head of the twin-screw extruder are: 220-240°C in zone 1, 250-260°C in zone 2, 250-260°C in zone 3, 250-270°C in zone 4, 250-270°C in zone 5, 220-240°C in zone 6, 220-240°C in zone 7, 240-260°C in zone 8, and 250-280°C in die head; the speed of the screw of the twin-screw extruder is 280-350 rpm; under the preferred process conditions, the components can interact with each other, thereby forming an SPS material with stable performance.
[0056] The present invention is now further described in detail by taking the formula and preparation method of a specific SPS material as an example.
[0057]
[0058] SPS material performance testing and evaluation:
[0059] The particle materials prepared in the above Examples 1-4 and Comparative Examples 1-2 were first dried in a blast oven at 100-120° C. for 2 hours, and then the dried particle materials were made into standard test specimens by injection molding. The material performance test data of Examples 1-4 and Comparative Examples 1-2 are shown in FIG. Figure 1 shown.
[0060] Among them, the tensile strength is tested according to ASTM D-638 standard, the specimen type is Type I, the specimen size (mm): (176±2) (length) × (12.6±0.2) (end width) × (3.05±0.2) (thickness), and the tensile speed is 50mm / min.
[0061] The notched impact strength is tested according to ASTM D-256. The specimen type is Type I, and the specimen size (mm): (63±2)×(12.45±0.2)×(3.1±0.2); the notch type is Type A, and the notch residual thickness is 1.9 mm.
[0062] The SPS material and the preparation method thereof provided by the present invention are introduced in detail above. Specific examples are used herein to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method and the core idea of the present invention. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation mode and the scope of application. In summary, the content of this specification should not be understood as limiting the present invention.
[0063] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0064] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high dielectric constant and low dielectric loss material, characterized in that: High dielectric constant and low dielectric loss materials include the following: SPS resin, with a weight percentage of 75-90%; Special fiber, the weight percentage is 5-50%; Toughening agent, content of which is 1-3% by weight; Nucleating agent, the weight percentage content is 0.1-0.5%; Lubricant, content by weight is 0.1-0.5%; Antioxidant, content by weight is 0.2-0.5%; Dielectric constant enhancer, the weight percentage content is 5-20%; Other materials, the weight percentage content is 0.6-2%.
2. The high dielectric constant and low dielectric loss material according to claim 1, characterized in that: The SPS resin is para-polystyrene. The dielectric properties of the SPS resin material are close to those of fluorine resins in engineering plastics, and the dielectric loss and dielectric constant are low, so the SPS resin material is suitable for use as a high-frequency component material.
3. The high dielectric constant and low dielectric loss material according to claim 1, characterized in that: The special fiber is a specially modified glass fiber; The dielectric constant of glass fiber is ε = 12-15; The dielectric loss tangent of glass fiber is tgδ=0.004; The breakdown voltage strength of glass fiber ranges from 63-119.5 kV, and glass fiber can maintain stable dielectric properties at high frequencies; Glass fiber has the properties of high dielectric constant and low dielectric loss at high frequencies of 1-10 GHz, while reducing the density of glass fiber, which is conducive to product miniaturization and portable applications.
4. The high dielectric constant and low dielectric loss material according to claim 1, characterized in that: The nucleating agent is a carboxylic acid calcium salt with a long carbon chain as the main component.
5. The high dielectric constant and low dielectric loss material according to claim 1, characterized in that: The lubricant is high temperature resistant silicone powder.
6. The high dielectric constant and low dielectric loss material according to claim 1, characterized in that: The antioxidant is triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl) acrylonitrile, tris(2,4-di-tert-butylphenol) phosphite or a mixture of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylphenyl) phosphite in a weight ratio of 1:
1.
7. The high dielectric constant and low dielectric loss material according to claim 1, characterized in that: The main raw materials of the dielectric constant enhancer are niobium pentoxide, cobalt tetroxide, nano barium titanate, a mixture of niobium pentoxide (Nb2O5) and cobalt tetroxide (Co3O4), barium titanate (BaTiO3, BT), zirconium oxide, and dielectric grade titanium dioxide as dopants; The dielectric constant of niobium pentoxide is high, ε=1000, the bonds between niobium pentoxide atoms are tight, and electrons tend to stay between atoms.
8. The high dielectric constant and low dielectric loss material according to claim 1, characterized in that: The other materials include a compatibilizer, and the compatibilizer is PPO grafted with maleic anhydride.
9. A high dielectric constant and low dielectric loss material according to any one of claims 1 to 8, characterized in that: A preparation method is also disclosed, and the specific steps are as follows: S1. Prepare materials; S2, preparing mixed materials; S3, extruding and granulating the mixture to obtain SPS material.
10. The method for preparing a high dielectric constant and low dielectric loss material according to claim 9, characterized in that: The mixed material is extruded and granulated by a twin-screw extruder; The temperature of the mixed material from the feeding port to the die of the twin-screw extruder is: zone 1 220-240°C, zone 2 250-260°C, zone 3 250-260°C, zone 4 250-270°C, zone 5 250-270°C, zone 6 220-240°C, zone 7 220-240°C, zone 8 240-260°C, and die head 250-280°C; The speed of the twin-screw extruder screw is 280-350 rpm.
Citation Information
Patent Citations
Flexible composite dielectric material with high dielectric constant and low dielectric loss
CN103408876A